Use of learning media through technology for biology education students - Indra Maulana; Risma Delima Harahap; Islamiani Safitri (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2022)
Education is a learning process in increasing the knowledge and insights possessed by these students. The existence of technology for biology education students can be useful for the learning process and as a learning medium. This type of research is qualitative with descriptive method. The population used is the sixth semester of Biology Education Students, the total sample is 35 people, the data collection technique is done by giving questionnaires, the questionnaires are given to students directly and through google form. The results of the study obtained from 5 indicators (1) The use of learning media applications through the use of technology obtained a percentage of 60.29%, (2) Increased motivation obtained a percentage of 59.78%, (3) Effectiveness obtained a percentage of 61.30%, (4) Learning Media obtained the percentage of 56.36%, (5) Interest in Using Technology obtained a percentage of 57.96%, With the existence of learning media through the use of technology, it can support the implementation of learning for students and can get better knowledge insights.AbstrakPendidikan merupakan suatu proses pembelajaran didalam menambah pengetahuan wawasan yang dimiliki oleh mahasiswa tersebut. dengan adanya Teknologi bagi  mahasiswa pendidikan biologi dapat bermanfaat untuk proses pembelajaran  dan sebagai  media pembelajaran Penelitian ini bertujuan untuk melihat dang mengetahui penggunaan media pembelajaran melalui pemanfaatan teknologi bagi mahasiswa  pendidikan biologi memiliki peran penting didalam menunjang pelaksanaan pembelajaran. Jenis Penelitian ini kualitatif dengan metode deskriptif. Populasi yang digunakan adalah Mahasiswa/i Pendidikan Biologi Semester enam,Total sempel berjumlah 35 orang, Tehnik pengumpulan data dilakukan dengan pemberian angket, Angket tersebut diberikan kepada Mahasiswa/i yang secara langsung dan melalui google form. Hasil Penelitian yang diperoleh dari 5 indikator (1) Penggunaan Aplikasi  media pembelajaran melalui pemanfaatan teknologi memperoleh persentase sebesar 60.29%, (2) Peningkatan Motivasi memperoleh persentase sebesar 59.78%, (3) Keefektifan memperoleh persentase sebesar 61.30%, (4) Media Pembelajaran memperoleh persentase sebesar 56.36%, (5) Minat Penggunaan Teknologi memperoleh persentase sebesar 57.96%, Dengan adanya media pembelajaran melalui  pemanfaatan teknologi  bisa menunjang  didalam pelaksanaan pembelajaran  bagi mahasiswa dan bisa mendapatkan wawasan  pengetahuan yang lebih baik.